Differences in the effects of Bordetella pertussis and respiratory syncytial virus infection on the composition of nasopharyngeal flora in neonates - Ding, Yijun; Wang, Qing; Li, Dongfang; Li, Yue; Yao, Kaihu; Wang, Tianyou (Frontiers in Pediatrics, 2023)
Bordetella pertussis and respiratory syncytial virus (RSV) are important pathogens causing cough in neonates. Few studies have investigated the differences in the effects of these two specific infections on respiratory flora. The aim of this study was to explore whether infections with Bordetella pertussis and RSV have different effects on respiratory floral composition in neonates. Nasopharyngeal respiratory flora was assessed by 16S ribosomal RNA amplification and V3–V4 region sequencing. Shannon and Simpson indices were calculated to determine the α diversity and principal coordinate analysis was performed to determine the β diversity. In total, 111 hospitalized neonates were divided into the pertussis (n=29), RSV (n=57), and control groups (n=25) according to the pathogens detected. The relative abundance of Bordetella was significantly higher in the pertussis group (median: 19.18%, interquartile range: 72.57%). In contrast, this species was not detected in the other two groups. In the RSV group, the relative abundance of Streptococcus (median: 77.15%, interquartile range: 45.84%) was significantly higher than those in the pertussis and control groups (both P<0.001). The α diversity of the RSV group was significantly lower than that of the control group (P<0.001). Moreover, no statistically significant differences in the Shannon and Simpson indices were observed between the pertussis and control groups (P=0.101 and P=0.202, respectively). Principal coordinate analysis revealed a large overlap between the pertussis and control groups and a significant distance between the RSV and control groups without any overlap. Thus, the effects of infections with the two species, B. pertussis and RSV, impacted the diversity of nasopharyngeal flora differently. The principles underlying the difference in the effects of different pathogens on microbial flora require further investigation.